2017
DOI: 10.1371/journal.pone.0173809
|View full text |Cite
|
Sign up to set email alerts
|

Co-ingestion of carbohydrate and whey protein increases fasted rates of muscle protein synthesis immediately after resistance exercise in rats

Abstract: The objective of the study was to investigate whether co-ingestion of carbohydrate and protein as compared with protein alone augments muscle protein synthesis (MPS) during early exercise recovery. Two months old rats performed 10 repetitions of ladder climbing with 75% of body weight attached to their tails. Placebo (PLA), whey protein (WP), or whey protein plus carbohydrate (CP) was then given to rats by gavage. An additional group of sedentary rats (SED) was used as controls. Blood samples were collected im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
7
1
Order By: Relevance
“…However, exercise did not result in significantly higher mixed muscle protein synthesis rates when compared to the sedentary rats (Figure 1). This finding is in contrast with some (Gasier et al, 2010;Kubica et al, 2005;Mosoni et al, 1995;Munoz et al, 1994;Wong & Booth, 1990;Ogasawara et al, 2016;Ogasawara et al, 2014), but not all (Katzeff et al, 1995;Wang et al, 2017) studies that have assessed the impact of exercise on mixed muscle protein synthesis rates in rats. The absence of a response may be explained by a relatively low (or negative) synthetic response of proteins residing outside of the myofibrillar and mitochondrial sub-fractions.…”
Section: Discussioncontrasting
confidence: 96%
“…However, exercise did not result in significantly higher mixed muscle protein synthesis rates when compared to the sedentary rats (Figure 1). This finding is in contrast with some (Gasier et al, 2010;Kubica et al, 2005;Mosoni et al, 1995;Munoz et al, 1994;Wong & Booth, 1990;Ogasawara et al, 2016;Ogasawara et al, 2014), but not all (Katzeff et al, 1995;Wang et al, 2017) studies that have assessed the impact of exercise on mixed muscle protein synthesis rates in rats. The absence of a response may be explained by a relatively low (or negative) synthetic response of proteins residing outside of the myofibrillar and mitochondrial sub-fractions.…”
Section: Discussioncontrasting
confidence: 96%
“…In our study, we employed high-intensity progressive RE protocol (ladder-climbing) and found increased FHL muscle mass and maximal weight carrying capacity of rats after 10 weeks. Ladder-climbing resistance training with progressive overloads has been demonstrated to increase muscular strength or maximal weight carrying capacity of rats even after 8 weeks [28, 31, 32]. The key finding of our study is that seaweed in combination with RE further enhances the weight carrying strength.…”
Section: Discussionmentioning
confidence: 49%
“…The need for this CHO:PRO combined intervention is justified by previous evidence regarding an increased muscle glycogen storage, muscle damage amelioration, and greater acute and chronic training adaptations in the above mentioned sport-workload context [ 2 ]. By addressing such mechanisms in detail, it is evident that the CHO:PRO mixture improves the acute recovery process via stimulation of muscle protein synthesis (MPS), as well as the activation of the target mechanism of rapamycin ( mTOR ), signalling a pathway [ 5 , 6 ] and a more effective glycogen storage via insulinotropic response [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%